Preparation method for injection molding of high-heat-conductivity copper heat dissipation material
Through electrolytic copper powder agglomeration and dispersion treatment, raw material powder preparation, injection molding and sintering technology, the problems of low utilization rate of radiator materials, complex structure and difficult preparation and high cost are solved, and the injection molding preparation of high-thermal copper heat dissipation materials are realized, which significantly improves the thermal conductivity, electrical conductivity and tensile properties of the material.
Patent Information
- Application Number
- CN202411927682.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2044-12-25
AI Technical Summary
In the prior art, the radiator processing materials have low utilization rates, complex structures and difficult to prepare, and high production costs. When adding alloy elements to improve thermal and electrical conductivity, the performance of the two cannot be improved in concert, making it difficult to prepare complex-shaped copper parts, and the operation is difficult.
Through various technical means such as electrolytic copper powder agglomeration and dispersion treatment, raw material powder preparation, injection molding, atmospheric sintering and hot isostatic sintering, injection molding and preparation of high-thermal copper heat dissipation materials, the injection molding and preparation of high-thermal copper heat dissipation materials are achieved. This method significantly improves sintering densification through the combination of powder particle size, atmosphere protection and densification, liquid phase sintering, activation sintering and thermal isostatic sintering.
The thermal conductivity, conductivity and strong plasticity of copper heat dissipation materials have been synergistically improved. The material density reaches more than 99%, the thermal conductivity is ≥365W/(m·K), and the conductivity can reach 90.5% IACS, meeting the performance requirements of copper radiators with high thermal conductivity complex structures.
Smart Images

Figure CN119819928A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of powder metallurgy, in particular to a preparation method of high thermal conductivity copper heat dissipation material by injection molding. Background Art
[0002] As the shape complexity increases, the heat sink is designed to transfer heat more efficiently. Copper has good electrical and thermal conductivity. The thermal conductivity of copper is about 401W / (m·k), which is about 1.7 times that of pure aluminum. The thermal expansion coefficient is also about 6×10 lower than that of pure aluminum. -6 / K. Copper materials not only integrate the thermal management material properties of high thermal conductivity and low thermal expansion coefficient, but also have good corrosion resistance, which largely solves the problem of easy wear and frequent maintenance of devices in high temperature and corrosive environments. Therefore, in certain circumstances, copper-based materials are often the first choice for thermal management materials.
[0003] Metal injection molding can provide a unique thermal management solution to dissipate heat from microelectronic devices. Metal injection molding allows the necessary design freedom and provides a cost-effective method to manufacture the large number of heat sinks required for electronic devices. Traditional production methods include extrusion, casting and machining; among them, extrusion is a highly automated, low-cost, high-volume process, but it inherently limits the geometry of the fins. Extrusion or die-casting can produce fins with a high gap ratio, but the cost is higher. Similarly, the performance of folded fin heat sinks is twice that of extruded heat sinks, but the cost is also increased. Machining and other methods have low material utilization, and the closely arranged pin-fin structure also makes the processing difficult. The low material utilization also makes large-scale manufacturing production cost high.
[0004] Chinese patent CN111996405A discloses a method for preparing high-strength and high-conductivity copper alloys by metal injection molding. This method requires the use of an internal oxidation method to prepare Al2O3 dispersed copper powder. Although Al2O3 dispersed copper powder can improve thermal conductivity to a certain extent, the improvement in thermal conductivity is not significant, and the electrical conductivity is not high, and the density is the same.
[0005] Chinese patent CN102554229A discloses a method for preparing gradient structure copper heat sink by injection molding. The method requires the use of two different copper powder gradations. The difficulty of two-cavity injection during the injection molding process is very large. Although sintering and pressure processing can densify the prepared heat sink, the fins of the heat sink are porous structure materials with a relative density between 50-96%, poor electrical conductivity, and uneven thermal conductivity of each part.
[0006] Chinese patent CN117926153A discloses a heat treatment method for preparing high-strength and high-conductivity copper alloys, which requires the use of directional solidification technology to solidify alloy plates with different texture directions layer by layer to form an overall alloy material stacked according to the soft and hard orientation rules, and then obtain a high-strength and high-conductivity copper alloy through a cyclic heat treatment method after rolling; the shape and method of the prepared material are limited, so it can be seen that copper parts with complex shapes cannot be prepared, and although the tensile strength of the prepared alloy material is improved by stacking according to the soft and hard orientation rules, the conductivity cannot reach 90% IACS.
[0007] Chinese patent CN101966587A discloses a method for preparing high-performance heat pipe copper powder, which requires first melting a high-purity electrolytic copper plate and then adding copper oxide powder, then sprinkling amorphous carbon powder into a crucible during atomization, and then performing a leak bag overall atomization to obtain powder, and finally drying, reducing, crushing and screening to obtain pure copper powder; although the pure copper powder can be used for the preparation of high-performance heat pipes, the preparation process of pure copper powder is complicated and difficult to operate, and the process of preparing high-performance heat pipes has high process cost and low efficiency, which is not conducive to industrial application. Summary of the invention
[0008] In order to solve the problems of low utilization rate of machining materials, complex and difficult to prepare structures, and high production costs of heat sinks in the prior art, if alloy elements are added to improve thermal conductivity and electrical conductivity, the two properties cannot be improved synergistically, complex copper parts cannot be prepared, and the operation is difficult, etc.; the present invention proposes a preparation method for injection molding of high thermal conductivity copper heat sink materials that can solve the above problems. The technical solution is as follows:
[0009] A method for preparing a high thermal conductivity copper heat dissipation material by injection molding, the method comprising the following steps:
[0010] S1. Agglomeration and dispersion treatment of electrolytic copper powder: weigh the electrolytic copper powder, and perform air flow crushing treatment and grinding treatment in sequence to obtain agglomerated and dispersed electrolytic copper powder;
[0011] S2, raw material powder preparation: the electrolytic copper powder, atomized copper powder and copper alloy powder agglomerated and dispersed in S1 are stirred and mixed uniformly to prepare raw material powder;
[0012] S3, injection molding: the S2 raw material powder and the plastic-based binder are subjected to high-temperature and high-speed internal kneading to obtain high-purity feedstock; the high-purity feedstock is then injection molded to obtain a green part with no defects, no deformation, and uniform composition; the green part is then subjected to catalytic degreasing and thermal degreasing to obtain a thermally degreased sample;
[0013] S4, atmospheric pressure sintering + hot isostatic pressing sintering: The sample after hot stripping in S3 is subjected to atmospheric pressure sintering in a hydrogen atmosphere and hot isostatic pressing sintering in a nitrogen atmosphere in turn to obtain a fully dense high thermal conductivity copper heat dissipation material.
[0014] Optionally, during the S1 air flow crushing process, the rotation speed of the classifying wheel is 9000-12000r / min; during the grinding process, 0.5% by mass of anhydrous ethanol and 1-1.5% of stearic acid are added, the electrolytic copper powder is ground at a pressure of 400-800Kpa, and the feed rate is 30-60g / min.
[0015] Optionally, the average particle size of the agglomerated and dispersed electrolytic copper powder in S1 is 15-25 μm.
[0016] Optionally, in the S2 raw material powder, the mass fraction of electrolytic copper powder is 20-40%, the mass fraction of atomized powder is 70-90%, and the mass fraction of copper-nickel alloy powder is 1-2%.
[0017] Optionally, the particle size of S2 electrolytic copper powder is less than or equal to 600 mesh, and D50 is 15-20µm; the particle size of atomized copper powder is 200-400 mesh, and D50 is 25-30µm; the copper alloy powder is a copper-nickel alloy, in which the mass fraction of nickel is 60%, the mass fraction of copper is 33%, and the mass fraction of iron is 7%.
[0018] Optionally, the mass fraction of polyoxymethylene in the plastic-based binder in S3 is 75-85%, the mass fraction of polyethylene is 8-10%, the mass fraction of polypropylene is 4-6%, the mass fraction of ethylene-vinyl acetate copolymer is 4-6%, and the mass fraction of stearic acid is 4-6%; argon is selected as the protective atmosphere for the mixing atmosphere.
[0019] Optionally, during the S3 injection process, the injection temperature is 180-190°C, the injection pressure is 90-120 bar, the injection speed is 40-80 mm / s, and the mold temperature is 110-130°C; the catalytic degreasing is used to remove polyoxymethylene, the main component of the binder; when the thermal degreasing is performed from room temperature to 500°C, the heating rate is 1°C / min, and the temperatures are kept at 200°C, 350°C, and 500°C for 30 minutes respectively.
[0020] Optionally, the degreasing rate of the sample after S3 thermal degreasing is 7.5-9.0% and the density is 5.20-5.80g / cm 3 .
[0021] Optionally, in the pressureless sintering step S4, the flow rate of the hydrogen gas is ≥ 2 m / s. 3 / min, the sintering temperature is 1060-1075℃, and the holding time is 4-6h; during hot isostatic pressing sintering, the temperature is kept at 900-950℃ for 1-3h in a nitrogen atmosphere.
[0022] Optionally, the S4 fully dense high thermal conductivity copper heat dissipation material has a density of 99.5-99.9%, a tensile strength of 185-210 MPa, a tensile strain at break of 40.5-48.2%, a thermal conductivity of 360-376 W / (m·K), and an electrical conductivity of 82.5-90.8% IACS.
[0023] Compared with the prior art, the above technical solution has at least the following beneficial effects:
[0024] The above scheme, the present invention proposes a preparation method of high thermal conductivity copper heat dissipation material injection molding, which can solve the problems of low utilization rate of machining materials, complex structure and difficult preparation, and high production cost of the radiator in the prior art. If alloy elements are added to improve the thermal conductivity and electrical conductivity, there will be technical problems such as the performance of the two cannot be improved synergistically, complex-shaped copper parts cannot be prepared, and the operation is difficult.
[0025] The preparation method of the present invention prevents the high activity and easy oxidation of copper, realizes the sintering activation effect of electrolytic copper powder and the liquid phase sintering effect of low-melting copper-nickel powder, the high shape retention of plastic-based system samples and the high degreasing rate of green billets, and also adopts a variety of mechanisms to promote sintering densification, such as hydrogen atmosphere sintering and hot isostatic pressing sintering, which can significantly improve sintering densification.
[0026] The present invention can greatly disperse the powder agglomeration through the electrolytic copper powder agglomeration and dispersion treatment, thereby improving the tap density, making it easier to be coated by the binder and increasing the powder loading capacity.
[0027] The present invention is prepared through raw material powder, and can make fine copper powder evenly filled and distributed among coarse copper powder. The combination with the binder is maximized by particle size matching, the distance between particles becomes smaller, and the sintering resistance becomes smaller under the condition of constant sintering activation energy, and the sintering efficiency is effectively improved. The addition of low melting point copper-nickel powder also reduces the sintering temperature, and liquid phase sintering is used to promote sintering densification, saving sintering energy and cost.
[0028] The present invention can integrate parts with complex structures through injection molding, with almost no material loss and a utilization rate of up to 98%, solving the problems of low utilization rate of radiator machining materials, complex and difficult preparation, and high production cost, and provides a new idea for the preparation of heat dissipation devices with high material costs and complex structures.
[0029] The present invention uses normal pressure sintering + hot isostatic pressing sintering, the grains grow fully, and the grains are tightly combined, and the sintered parts are fully dense, thereby obtaining excellent comprehensive performance, high thermal conductivity and electrical conductivity, and good tensile performance, meeting the use requirements of the radiator.
[0030] The copper heat dissipation material prepared by the present invention has a density of more than 99%, a thermal conductivity of ≥365W / (m·K), an electrical conductivity of up to 90.5% IACS, and has excellent thermal and electrical conductivity. The copper sample fracture tensile strain can reach 45.78%, and the tensile strength is 164.43MPa. It has good ductility and tensile resistance, is not prone to fracture and damage, and can meet the performance requirements of high thermal conductivity complex structure copper heat sinks.
[0031] In summary, compared with other traditional methods, the method of the present invention realizes the preparation of integrated needle-shaped heat dissipation materials through various mechanisms that promote sintering densification, such as powder particle size matching, atmosphere protection mixing, liquid phase sintering, activated sintering, and hot isostatic pressing sintering. The thermal conductivity, electrical conductivity, and strength and plasticity of the copper heat dissipation material are synergistically improved. The method is simple and easy to operate, green and environmentally friendly, low in cost, short in process, and high in efficiency. It meets the preparation requirements of high thermal conductivity, large-size, complex structure copper heat dissipation materials, and is conducive to large-scale industrial production and promotion. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0033] Figure 1 It is a process flow chart of a preparation method of a high thermal conductivity copper heat dissipation material injection molding of the present invention;
[0034] Figure 2 This is a microstructure diagram of a copper heat dissipation material prepared by a method for preparing a high thermal conductivity copper heat dissipation material by injection molding according to Example 1 of the present invention;
[0035] Figure 3 This is a microstructure diagram of a copper heat dissipation material prepared by a preparation method of a high thermal conductivity copper heat dissipation material by injection molding according to Example 2 of the present invention. DETAILED DESCRIPTION
[0036] The technical solution of the present invention is described below in conjunction with the accompanying drawings.
[0037] In the embodiments of the present invention, words such as "exemplarily" and "for example" are used to indicate examples, illustrations or explanations. Any embodiment or design described as "example" in the present invention should not be interpreted as being more preferred or more advantageous than other embodiments or designs. Specifically, the use of the word "example" is intended to present the concept in a specific way. In addition, in the embodiments of the present invention, the meaning expressed by "and / or" can be both, or it can be either of the two.
[0038] In the embodiments of the present invention, "image" and "picture" may sometimes be used interchangeably. It should be noted that when the distinction between them is not emphasized, the meanings they intend to express are consistent.
[0039] In the embodiments of the present invention, sometimes a subscript such as W1 may be written as a non-subscript such as W1. When the difference is not emphasized, the meanings to be expressed are the same.
[0040] In order to make the technical problems, technical solutions and advantages to be solved by the present invention more clear, a detailed description will be given below with reference to the accompanying drawings and specific embodiments.
[0041] A method for preparing a high thermal conductivity copper heat dissipation material by injection molding, the method for preparing a high thermal conductivity copper heat dissipation material by injection molding is combined with Figure 1 Follow these steps:
[0042] S1. Agglomeration and dispersion treatment of electrolytic copper powder: weigh the electrolytic copper powder, and perform air flow crushing treatment and grinding treatment in sequence to obtain agglomerated and dispersed electrolytic copper powder;
[0043] S2, raw material powder preparation: the electrolytic copper powder, atomized copper powder and copper alloy powder agglomerated and dispersed in S1 are stirred and mixed uniformly to prepare raw material powder;
[0044] S3, injection molding: the S2 raw material powder and the plastic-based binder are subjected to high-temperature and high-speed internal kneading to obtain high-purity feedstock; the high-purity feedstock is then injection molded to obtain a green part with no defects, no deformation, and uniform composition; the green part is then subjected to catalytic degreasing and thermal degreasing to obtain a thermally degreased sample;
[0045] S4, atmospheric pressure sintering + hot isostatic pressing sintering: The sample after hot stripping in S3 is subjected to atmospheric pressure sintering in a hydrogen atmosphere and hot isostatic pressing sintering in a nitrogen atmosphere in turn to obtain a fully dense high thermal conductivity copper heat dissipation material.
[0046] In particular, during the S1 air flow crushing process, the rotating speed of the classifying wheel is 9000-12000 r / min; during the grinding process, 0.5% by mass of anhydrous ethanol and 1-1.5% of stearic acid are added, the electrolytic copper powder is ground at a pressure of 400-800 Kpa, and the feed rate is 30-60 g / min.
[0047] In particular, the average particle size of the agglomerated and dispersed electrolytic copper powder in S1 is 15-20 μm.
[0048] In particular, in the S2 raw material powder, the mass fraction of electrolytic copper powder is 20-40%, the mass fraction of atomized powder is 70-90%, and the mass fraction of copper-nickel alloy powder is 1-2%.
[0049] In particular, the particle size of S2 electrolytic copper powder is less than or equal to 600 mesh, and D50 is 15-20µm; the particle size of atomized copper powder is 200-400 mesh, and D50 is 25-30µm; the copper alloy powder is a copper-nickel alloy, in which the mass fraction of nickel is 60%, the mass fraction of copper is 33%, and the mass fraction of iron is 7%.
[0050] In particular, the mass fraction of polyoxymethylene in the plastic-based binder in S3 is 75-85%, the mass fraction of polyethylene is 8-10%, the mass fraction of polypropylene is 4-6%, the mass fraction of ethylene-vinyl acetate copolymer is 4-6%, and the mass fraction of stearic acid is 4-6%; argon is selected as the protective atmosphere for the mixing atmosphere.
[0051] In particular, during the S3 injection process, the injection temperature is 180-190°C, the injection pressure is 90-120 bar, the injection speed is 40-80 mm / s, and the mold temperature is 110-130°C; the main component of the binder removed by catalytic degreasing is polyoxymethylene; when thermal degreasing is performed from room temperature to 500°C, the heating rate is 1°C / min, and the temperatures are kept at 200°C, 350°C, and 500°C for 30 minutes respectively.
[0052] In particular, the degreasing rate of the S3 samples after thermal degreasing was 7.5-9.0% and the density was 5.20-5.80 g / cm 3 .
[0053] In particular, in the S4 pressureless sintering step, the flow rate of the hydrogen gas is ≥ 2m 3 / min, the sintering temperature is 1060-1075℃, and the holding time is 4-6h; during hot isostatic pressing sintering, the temperature is kept at 900-950℃ for 1-3h in a nitrogen atmosphere.
[0054] In particular, the S4 fully dense high thermal conductivity copper heat dissipation material has a density of 99.5-99.9%, a tensile strength of 185-210 MPa, a tensile strain at break of 40.5-48.2%, a thermal conductivity of 360-376 W / (m·K), and an electrical conductivity of 82.5-90.8% IACS.
[0055] Example 1
[0056] A method for preparing a high thermal conductivity copper heat dissipation material by injection molding, the method comprising the following steps:
[0057] S1. Agglomeration and dispersion treatment of electrolytic copper powder: 3000 g of 600-mesh electrolytic copper powder was weighed and subjected to air flow crushing treatment. The speed of the classifying wheel was 10000 r / min. After 2 h of air flow crushing treatment, the average particle size of the electrolytic copper powder was 18.20 μm. Then, 0.5% by mass of anhydrous ethanol and 1.0% by mass of stearic acid were added. The electrolytic copper powder was ground under a grinding pressure of 600 Kpa and a feed rate of 40 g / min to obtain agglomerated and dispersed electrolytic copper powder with an average particle size of 17.50 μm.
[0058] S2. Preparation of raw material powder: The electrolytic copper powder, atomized copper powder and copper-nickel alloy powder agglomerated and dispersed in S1 are stirred and mixed evenly in a mixer at room temperature in a ratio of 28:70:2 to prepare raw material powder; wherein the particle size of the electrolytic copper powder is less than or equal to 600 mesh, and D50 is 17.50µm; the particle size of the atomized copper powder is 325 mesh, and D50 is 26.80µm; the mass fraction of nickel in the copper-nickel alloy powder is 60%, the mass fraction of copper is 33%, and the mass fraction of iron is 7%;
[0059] S3, injection molding: S2 raw material powder and plastic-based binder (polyoxymethylene 85wt.%, polyethylene 5wt.%, polypropylene 4 wt.%, ethylene-vinyl acetate copolymer 3wt.%, stearic acid 3wt.%) are kneaded at 185°C and 30r / min for 60min in a volume ratio of 58:42, and argon is selected as a protective atmosphere in the kneading atmosphere to obtain a high-purity feed; then, the high-purity feed is injection molded using an injection molding machine and a matching mold to obtain a radiator green body with no defects, no deformation and uniform composition; then, the radiator green body is catalytically degreased and thermally degreased to obtain a thermally degreased sample; during the injection process, the injection temperature is 185°C, the injection pressure is 100bar, the injection speed is 60mm / s, and the mold temperature is 120°C; the main component of the binder removed by catalytic degreasing is polyoxymethylene; when thermal degreasing is performed from room temperature to 500°C, the heating rate is 1°C / min, and the samples are kept at 200°C, 350°C and 500°C for 30min respectively; the degreasing rate of the sample after thermal degreasing is 7.8%, and the density is 5.54gcm 3 ;
[0060] S4, atmospheric pressure sintering + hot isostatic pressing sintering: The sample after hot stripping in S3 was subjected to atmospheric pressure sintering in hydrogen atmosphere and hot isostatic pressing sintering in nitrogen atmosphere in sequence. In the atmospheric pressure sintering step, the flow rate of the hydrogen introduced was 2m / s. 3 / min, heat up to 500℃ at a rate of 1℃ / min, then heat up to 1070℃ at a rate of 2℃ / min after 500℃, and then keep warm for 150min; during hot isostatic pressing sintering, pressurized re-firing is carried out in the hot isostatic pressing furnace, the temperature is increased to 900℃ at 5℃ / min, sintered at a pressure of 100MPa for 90min, and then kept warm and pressurized for 30min. After sintering, it is cooled at 2.3℃ / min to obtain a fully dense high thermal conductivity copper heat dissipation material.
[0061] like Figure 2 As shown, the fully dense high thermal conductivity copper heat dissipation material prepared in this embodiment is in the shape of needle-shaped closely arranged columns and an integrated substrate, with a density of 99.5%, a tensile strength of 192 MPa, a tensile strain at break of 40.5%, a thermal conductivity of 362 W / (m·K), and an electrical conductivity of 82.5% IACS.
[0062] Comparative Example 1 is a method for preparing high-strength and high-conductivity copper alloy by metal injection molding, which is disclosed in Chinese patent CN111996405A. This method requires the use of internal oxidation to prepare Al2O3 dispersed copper powder. The advantages of the metal injection molding method are brought into play, and parts with complex shapes can be prepared. At the same time, the problem of loose sintering of Al2O3 dispersed copper powder can be improved, and the thermal and electrical conductivity can be effectively improved.
[0063] By comparing Example 1 and Comparative Example 1, it can be seen that the addition of Al2O3 plays a role in dispersion strengthening copper, which greatly improves the yield strength of the material, but cannot maximize the improvement of thermal conductivity and electrical conductivity, and the dispersion effect affects the excellent ductility of copper, the thermal conductivity is not much improved, the electrical conductivity is not high, and the density is the same. The present invention maximizes the combination of powder particles and binder through the grading effect of coarse and fine copper powder, and the sintering efficiency is also effectively improved. The addition of low melting point copper-nickel powder also reduces the sintering temperature, and liquid phase sintering is used to promote sintering densification. Through normal pressure + hot isostatic pressing sintering, full sintering densification is achieved, and the excellent thermal and electrical conductivity of copper is maximized.
[0064] Example 2
[0065] A method for preparing a high thermal conductivity copper heat dissipation material by injection molding, the method comprising the following steps:
[0066] S1. Agglomeration and dispersion treatment of electrolytic copper powder: 4000 g of 600-mesh electrolytic copper powder was weighed and subjected to air flow crushing treatment. The speed of the classifying wheel was 12000 r / min. After 3 h of air flow crushing treatment, the average particle size of the electrolytic copper powder was 15.5 μm. Then, 0.5% by mass of anhydrous ethanol and 1.5% by mass of stearic acid were added. The electrolytic copper powder was ground under a grinding pressure of 800 Kpa and a feed rate of 50 g / min to obtain agglomerated and dispersed electrolytic copper powder with an average particle size of 15.20 μm.
[0067] S2. Preparation of raw material powder: The electrolytic copper powder, atomized copper powder and copper-nickel alloy powder agglomerated and dispersed in S1 are stirred and mixed evenly in a mixer at room temperature in a ratio of 28:70:2 to prepare raw material powder; wherein the particle size of the electrolytic copper powder is less than or equal to 600 mesh, and D50 is 15.20µm; the particle size of the atomized copper powder is 350 mesh, and D50 is 25.3µm; the mass fraction of nickel in the copper-nickel alloy powder is 60%, the mass fraction of copper is 33%, and the mass fraction of iron is 7%;
[0068] S3, injection molding: S2 raw material powder and plastic-based binder (polyoxymethylene 85wt.%, polyethylene 5wt.%, polypropylene 4wt.%, ethylene-vinyl acetate copolymer 3wt.%, stearic acid 3wt.%) are kneaded at 185°C and 30r / min for 60min in a volume ratio of 55:45, and argon is selected as the protective atmosphere to obtain high-purity feed; then the high-purity feed is injection molded using an injection molding machine and a matching mold to obtain a defect-free, deformation-free, and uniformly composed radiator green body; then The radiator green body was subjected to catalytic debinding and thermal debinding to obtain the samples after thermal debinding. During the injection process, the injection temperature was 190°C, the injection pressure was 120 bar, the injection speed was 40 mm / s, and the mold temperature was 130°C. The main component of the binder removed by catalytic debinding was polyoxymethylene. When thermal debinding was performed from room temperature to 500°C, the heating rate was 1°C / min, and the samples were kept at 200°C, 350°C, and 500°C for 30 minutes respectively. The debinding rate of the sample after thermal debinding was 8.8%, and the density was 5.70 g / cm 3 ;
[0069] S4, atmospheric pressure sintering + hot isostatic pressing sintering: The sample after hot stripping in S3 was subjected to atmospheric pressure sintering in hydrogen atmosphere and hot isostatic pressing sintering in nitrogen atmosphere in sequence. In the atmospheric pressure sintering step, the flow rate of the hydrogen introduced was 2m / s. 3 / min, heat up to 500℃ at a rate of 1℃ / min, then heat up to 1070℃ at a rate of 2℃ / min after 500℃, and then keep warm for 150min; during hot isostatic pressing sintering, pressurized re-firing is carried out in the hot isostatic pressing furnace, the temperature is increased to 900℃ at 5℃ / min, sintered at a pressure of 100MPa for 90min, and then kept warm and pressurized for 30min. After sintering, it is cooled at 2.5℃ / min to obtain a fully dense high thermal conductivity copper heat dissipation material.
[0070] like Figure 3 As shown, the fully dense high thermal conductivity copper heat dissipation material prepared in this embodiment is in the shape of needle-shaped closely arranged columns and an integrated substrate, with a density of 99.9%, a tensile strength of 209.8 MPa, a tensile strain at break of 48.2%, a thermal conductivity of 376 W / (m·K), and an electrical conductivity of 90.8% IACS.
[0071] Example 3
[0072] A method for preparing a high thermal conductivity copper heat dissipation material by injection molding, the method comprising the following steps:
[0073] S1. Agglomeration and dispersion treatment of electrolytic copper powder: 200 g of 600-mesh electrolytic copper powder was weighed and subjected to air flow crushing treatment. The speed of the classifying wheel was 9000 r / min. After 3 h of air flow crushing treatment, the average particle size of the electrolytic copper powder was 19.8 μm. Then, 0.5% by mass of anhydrous ethanol and 1.2% by mass of stearic acid were added. The electrolytic copper powder was ground under a grinding pressure of 400 Kpa and a feed rate of 30 g / min to obtain agglomerated and dispersed electrolytic copper powder with an average particle size of 18.9 μm.
[0074] S2. Preparation of raw material powder: The electrolytic copper powder, atomized copper powder and copper-nickel alloy powder agglomerated and dispersed in S1 are stirred and mixed evenly in a mixer at room temperature in a ratio of 20:78:2 to prepare raw material powder; wherein the particle size of the electrolytic copper powder is less than or equal to 700 mesh, and D50 is 18.9µm; the particle size of the atomized copper powder is 275 mesh, and D50 is 30.0µm; the mass fraction of nickel in the copper-nickel alloy powder is 60%, the mass fraction of copper is 33%, and the mass fraction of iron is 7%;
[0075] S3, injection molding: S2 raw material powder and plastic-based binder (polyoxymethylene 75wt.%, polyethylene 10wt.%, polypropylene 5wt.%, ethylene-vinyl acetate copolymer 5wt.%, stearic acid 5wt.%) are kneaded at 180°C and 30r / min for 60min in a volume ratio of 63:37, and argon is selected as the protective atmosphere to obtain high-purity feed; then the high-purity feed is injection molded using an injection molding machine and a matching mold to obtain a defect-free, deformation-free, uniformly composed radiator green body; then The radiator green body was subjected to catalytic debinding and thermal debinding to obtain the samples after thermal debinding. During the injection process, the injection temperature was 180°C, the injection pressure was 90 bar, the injection speed was 45 mm / s, and the mold temperature was 115°C. The main component of the binder removed by catalytic debinding was polyoxymethylene. When thermal debinding was performed from room temperature to 500°C, the heating rate was 1°C / min, and the samples were kept at 200°C, 350°C, and 500°C for 30 minutes respectively. The debinding rate of the sample after thermal debinding was 7.5%, and the density was 5.25 g / cm 3 ;
[0076] S4, atmospheric pressure sintering + hot isostatic pressing sintering: The sample after hot stripping in S3 was subjected to atmospheric pressure sintering in hydrogen atmosphere and hot isostatic pressing sintering in nitrogen atmosphere in sequence. In the atmospheric pressure sintering step, the flow rate of the hydrogen introduced was 2m / s. 3 / min, heat up to 500℃ at a rate of 1℃ / min, then heat up to 1070℃ at a rate of 2℃ / min after 500℃, and then keep warm for 150min; during hot isostatic pressing sintering, pressurized re-firing is carried out in the hot isostatic pressing furnace, the temperature is increased to 900℃ at 5℃ / min, sintered at a pressure of 100MPa for 60min, and then kept warm and pressurized for 30min. After sintering, it is cooled at 3.0℃ / min to obtain a fully dense high thermal conductivity copper heat dissipation material.
[0077] The fully dense high thermal conductivity copper heat dissipation material prepared in this embodiment is in the shape of needle-shaped closely arranged columns and an integrated substrate, with a density of 99.6%, a tensile strength of 195 MPa, a tensile strain at break of 42.1%, a thermal conductivity of 365 W / (m·K), and an electrical conductivity of 85.5% IACS.
[0078] Example 4
[0079] A method for preparing a high thermal conductivity copper heat dissipation material by injection molding, the method comprising the following steps:
[0080] S1. Agglomeration and dispersion treatment of electrolytic copper powder: 2000 g of 600-mesh electrolytic copper powder was weighed and subjected to air flow crushing treatment. The speed of the classifying wheel was 11000 r / min. After 1.5 h of air flow crushing treatment, the average particle size of the electrolytic copper powder was 18.9 μm. Then, 0.5% by mass of anhydrous ethanol and 1.1% by mass of stearic acid were added. The electrolytic copper powder was ground under a grinding pressure of 450 Kpa and a feed rate of 35 g / min to obtain agglomerated and dispersed electrolytic copper powder with an average particle size of 18.2 μm.
[0081] S2. Preparation of raw material powder: The electrolytic copper powder, atomized copper powder and copper-nickel alloy powder agglomerated and dispersed in S1 are stirred and mixed uniformly in a mixer at room temperature in a mass ratio of 27:72:1 to prepare raw material powder; wherein the particle size of the electrolytic copper powder is less than or equal to 650 mesh, and D50 is 18.2µm; the particle size of the atomized copper powder is 290 mesh, and D50 is 29.0µm and 600 mesh, and D50 is 10-15µm; the mass fraction of nickel in the copper-nickel alloy powder is 60%, the mass fraction of copper is 33%, and the mass fraction of iron is 7%;
[0082] S3, injection molding: the S2 raw material powder and the plastic-based binder (polyoxymethylene accounts for 82wt.%, polyethylene 9wt.%, polypropylene 3wt.%, ethylene-vinyl acetate copolymer 3wt.%, stearic acid 4wt.%) are kneaded at 183°C and 35r / min for 90min in a volume ratio of 62:38, and argon is selected as the protective atmosphere for the kneading atmosphere to obtain high-purity feed; then the high-purity feed is injection molded using an injection molding machine and a matching mold to obtain a defect-free, deformation-free, and uniformly composed radiator green piece; After that, the radiator green body was subjected to catalytic debinding and thermal debinding to obtain the sample after thermal debinding. During the injection process, the injection temperature was 183℃, the injection pressure was 95bar, the injection speed was 65mm / s, and the mold temperature was 125℃. The main component of the binder removed by catalytic debinding was polyoxymethylene. When thermal debinding was performed from room temperature to 500℃, the heating rate was 1℃ / min, and the samples were kept at 200℃, 350℃, and 500℃ for 30min respectively. The debinding rate of the sample after thermal debinding was 7.9%, and the density was 5.65 g / cm 3 ;
[0083] S4, atmospheric pressure sintering + hot isostatic pressing sintering: The sample after hot stripping in S3 was subjected to atmospheric pressure sintering in hydrogen atmosphere and hot isostatic pressing sintering in nitrogen atmosphere in sequence. In the atmospheric pressure sintering step, the flow rate of the hydrogen introduced was 2.5 m / s. 3 / min, heat up to 500℃ at a rate of 1℃ / min, then heat up to 1070℃ at a rate of 1.5℃ / min, and then keep warm for 150min; during hot isostatic pressing sintering, pressurized re-firing is carried out in the hot isostatic pressing furnace, the temperature is increased to 930℃ at 6℃ / min, and sintered at a pressure of 120MPa for 150min. After sintering, the temperature is cooled at 3.5℃ / min to obtain a fully dense high thermal conductivity copper heat dissipation material.
[0084] The fully dense high thermal conductivity copper heat dissipation material prepared in this embodiment is in the shape of needle-shaped closely arranged columns and an integrated substrate, with a density of 99.8%, a tensile strength of 208 MPa, a tensile strain at break of 46.2%, a thermal conductivity of 373 W / (m·K), and an electrical conductivity of 90.2% IACS.
[0085] Example 5
[0086] A method for preparing a high thermal conductivity copper heat dissipation material by injection molding, the method comprising the following steps:
[0087] S1. Agglomeration and dispersion treatment of electrolytic copper powder: 2500 g of 600-mesh electrolytic copper powder was weighed and subjected to air flow crushing treatment. The speed of the classifying wheel was 10500 r / min. After 3 h of air flow crushing treatment, the average particle size of the electrolytic copper powder was 17.20 μm. Then, 0.5% by mass of anhydrous ethanol and 1.3% by mass of stearic acid were added. The electrolytic copper powder was ground under a grinding pressure of 550 Kpa and a feed rate of 55 g / min to obtain agglomerated and dispersed electrolytic copper powder with an average particle size of 15.80 μm.
[0088] S2. Preparation of raw material powder: The electrolytic copper powder, atomized copper powder and copper-nickel alloy powder agglomerated and dispersed in S1 are stirred and mixed evenly in a mixer at room temperature in a ratio of 28:70:2 to prepare raw material powder; wherein the particle size of the electrolytic copper powder is less than or equal to 600 mesh, and D50 is 15.80µm; the particle size of the atomized copper powder is 310 mesh, and D50 is 27.50µm; the mass fraction of nickel in the copper-nickel alloy powder is 60%, the mass fraction of copper is 33%, and the mass fraction of iron is 7%;
[0089] S3, injection molding: S2 raw material powder and plastic-based binder (polyoxymethylene 85wt.%, polyethylene 5wt.%, polypropylene 4wt.%, ethylene-vinyl acetate copolymer 4wt.%, stearic acid 2wt.%) are kneaded at 188°C and 40r / min in a volume ratio of 55:44 for 80min, and argon is selected as the protective atmosphere to obtain high-purity feed; then the high-purity feed is injection molded using an injection molding machine and a matching mold to obtain a defect-free, deformation-free, uniformly composed radiator green body; then the powder is kneaded into a mold and molded into a mold; The green parts of the heat exchanger were subjected to catalytic debinding and thermal debinding to obtain the samples after thermal debinding. During the injection process, the injection temperature was 188°C, the injection pressure was 95 bar, the injection speed was 70 mm / s, and the mold temperature was 118°C. The main component of the binder removed by catalytic debinding was polyoxymethylene. When thermal debinding was performed from room temperature to 500°C, the heating rate was 1°C / min, and the samples were kept at 200°C, 350°C, and 500°C for 30 minutes respectively. The debinding rate of the sample after thermal debinding was 8.05%, and the density was 5.70 g / cm 3 ;
[0090] S4, atmospheric pressure sintering + hot isostatic pressing sintering: The sample after hot stripping in S3 was subjected to atmospheric pressure sintering in hydrogen atmosphere and hot isostatic pressing sintering in nitrogen atmosphere in sequence. In the atmospheric pressure sintering step, the flow rate of the hydrogen introduced was 2.5 m / s. 3 / min, heat up to 450℃ at a rate of 1.5℃ / min, heat up to 1075℃ at a rate of 2℃ / min after 450℃, and then keep warm for 120min; during hot isostatic pressing sintering, pressurized re-firing is carried out in the hot isostatic pressing furnace, the temperature is increased to 940℃ at 4℃ / min, and sintered at 90MPa pressure for 90min. After sintering, the temperature is cooled to room temperature at a rate of 2.8℃ / min to obtain a fully dense and high thermal conductivity copper heat dissipation material.
[0091] The fully dense high thermal conductivity copper heat dissipation material prepared in this embodiment is in the shape of needle-shaped closely arranged columns and an integrated substrate, with a density of 99.7%, a tensile strength of 201 MPa, a tensile strain at break of 44.2%, a thermal conductivity of 368 W / (m·K), and an electrical conductivity of 87.6% IACS.
[0092] Example 6
[0093] A method for preparing a high thermal conductivity copper heat dissipation material by injection molding, the method comprising the following steps:
[0094] S1. Agglomeration and dispersion treatment of electrolytic copper powder: 3000 g of 500-mesh electrolytic copper powder was weighed and subjected to air flow crushing treatment. The speed of the classifying wheel was 9500 r / min. After 2.5 h of air flow crushing treatment, the average particle size of the electrolytic copper powder was 17.8 μm. Then, 0.5% by mass of anhydrous ethanol and 1.3% by mass of stearic acid were added. The electrolytic copper powder was ground under a grinding pressure of 550 Kpa. The feed rate was 35 g / min to obtain agglomerated and dispersed electrolytic copper powder with an average particle size of 17.0 μm.
[0095] S2. Preparation of raw material powder: The electrolytic copper powder, atomized copper powder and copper-nickel alloy powder agglomerated and dispersed in S1 are stirred and mixed evenly in a mixer at room temperature according to a ratio of 25:74:1 to prepare raw material powder; wherein the particle size of the electrolytic copper powder is less than or equal to 600 mesh, and D50 is 17.8µm; the particle size of the atomized copper powder is 350 mesh, and D50 is 25.5µm; the mass fraction of nickel in the copper-nickel alloy powder is 60%, the mass fraction of copper is 33%, and the mass fraction of iron is 7%;
[0096] S3, injection molding: S2 raw material powder and plastic-based binder (polyoxymethylene 85%, polyethylene 8wt.%, polypropylene 3wt.%, ethylene-vinyl acetate copolymer 2wt.%, stearic acid 2wt.%) are mixed at a volume ratio of 65:35 at 182°C and 35r / min for 100min, and argon is selected as the protective atmosphere to obtain high-purity feed; then the high-purity feed is injected into an injection molding machine and a matching mold to obtain a defect-free, deformation-free, uniformly composed radiator green body; then the heat sink is The green parts of the device were subjected to catalytic debinding and thermal debinding to obtain samples after thermal debinding; during the injection process, the injection temperature was 182°C, the injection pressure was 115 bar, the injection speed was 55 mm / s, and the mold temperature was 115°C; the main component of the binder removed by catalytic debinding was polyoxymethylene; when thermal debinding was performed from room temperature to 500°C, the heating rate was 1°C / min, and the samples were kept at 200°C, 350°C, and 500°C for 30 minutes respectively; the debinding rate of the sample after thermal debinding was 8.3%, and the density was 5.72 g / cm 3 ;
[0097] S4, atmospheric pressure sintering + hot isostatic pressing sintering: The sample after hot stripping in S3 was subjected to atmospheric pressure sintering in hydrogen atmosphere and hot isostatic pressing sintering in nitrogen atmosphere in sequence. In the atmospheric pressure sintering step, the flow rate of the hydrogen introduced was 2.2 m / s. 3 / min, heat up to 650℃ at a rate of 1.2℃ / min, then heat up to 1072℃ at a rate of 1.8℃ / min, and then keep warm for 180min; during hot isostatic pressing sintering, pressurized re-firing is carried out in the hot isostatic pressing furnace, the temperature is increased to 940℃ at 4.2℃ / min, and sintered at a pressure of 115MPa for 150min. After sintering, it can be cooled in the furnace to obtain a fully dense high thermal conductivity copper heat dissipation material.
[0098] The fully dense high thermal conductivity copper heat dissipation material prepared in this embodiment is in the shape of needle-shaped closely arranged columns and an integrated substrate, with a density of 99.6%, a tensile strength of 193.6 MPa, a tensile strain at break of 41.3%, a thermal conductivity of 360 W / (m·K), and an electrical conductivity of %IACS.
[0099] The above scheme, the present invention proposes a preparation method of high thermal conductivity copper heat dissipation material injection molding, which can solve the problems of low utilization rate of machining materials, complex structure and difficult preparation, and high production cost of the radiator in the prior art. If alloy elements are added to improve the thermal conductivity and electrical conductivity, there will be technical problems such as the performance of the two cannot be improved synergistically, complex-shaped copper parts cannot be prepared, and the operation is difficult.
[0100] The preparation method of the present invention prevents the high activity and easy oxidation of copper, realizes the sintering activation effect of electrolytic copper powder and the liquid phase sintering effect of low-melting copper-nickel powder, the high shape retention of plastic-based system samples and the high degreasing rate of green billets, and also adopts a variety of mechanisms to promote sintering densification, such as hydrogen atmosphere sintering and hot isostatic pressing sintering, which can significantly improve sintering densification.
[0101] The present invention can greatly disperse the powder agglomeration through the electrolytic copper powder agglomeration and dispersion treatment, thereby improving the tap density, making it easier to be coated by the binder and increasing the powder loading capacity.
[0102] The present invention is prepared through raw material powder, and can make fine copper powder evenly filled and distributed among coarse copper powder. The combination with the binder is maximized by particle size matching, the distance between particles becomes smaller, and the sintering resistance becomes smaller under the condition of constant sintering activation energy, and the sintering efficiency is effectively improved. The addition of low melting point copper-nickel powder also reduces the sintering temperature, and liquid phase sintering is used to promote sintering densification, saving sintering energy and cost.
[0103] The present invention can integrate parts with complex structures through injection molding, with almost no material loss and a utilization rate of up to 98%, solving the problems of low utilization rate of radiator machining materials, complex and difficult preparation, and high production cost, and provides a new idea for the preparation of heat dissipation devices with high material costs and complex structures.
[0104] The present invention uses normal pressure sintering + hot isostatic pressing sintering, the grains grow fully, and the grains are tightly combined, and the sintered parts are fully dense, thereby obtaining excellent comprehensive performance, high thermal conductivity and electrical conductivity, and good tensile performance, meeting the use requirements of the radiator.
[0105] The copper heat dissipation material prepared by the present invention has a density of more than 99%, a thermal conductivity of ≥365W / (m·K), an electrical conductivity of up to 90.5% IACS, and has excellent thermal and electrical conductivity. The copper sample fracture tensile strain can reach 45.78%, and the tensile strength is 164.43MPa. It has good ductility and tensile resistance, is not prone to fracture and damage, and can meet the performance requirements of high thermal conductivity complex structure copper heat sinks.
[0106] In summary, compared with other traditional methods, the method of the present invention realizes the preparation of integrated needle-shaped heat dissipation materials through various mechanisms that promote sintering densification, such as powder particle size matching, atmosphere protection mixing, liquid phase sintering, activated sintering, and hot isostatic pressing sintering. The thermal conductivity, electrical conductivity, and strength and plasticity of the copper heat dissipation material are synergistically improved. The method is simple and easy to operate, green and environmentally friendly, low in cost, short in process, and high in efficiency. It meets the preparation requirements of high thermal conductivity, large-size, complex structure copper heat dissipation materials, and is conducive to large-scale industrial production and promotion.
[0107] It should be understood that the term "and / or" in this article is only a description of the association relationship of associated objects, indicating that there can be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship, but it may also indicate an "and / or" relationship. Please refer to the context for specific understanding.
[0108] In the present invention, "at least one" means one or more, and "plurality" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, at least one of a, b, or c can mean: a, b, c, ab, ac, bc, or abc, where a, b, and c can be single or multiple.
[0109] It should be understood that in various embodiments of the present invention, the size of the serial numbers of the above-mentioned processes does not mean the order of execution. The execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present invention.
[0110] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A method for preparing a high thermal conductivity copper heat dissipation material by injection molding, characterized in that: The preparation method of the high thermal conductivity copper heat dissipation material by injection molding is as follows: S1. Agglomeration and dispersion treatment of electrolytic copper powder: weigh the electrolytic copper powder, and perform air flow crushing treatment and grinding treatment in sequence to obtain agglomerated and dispersed electrolytic copper powder; S2, raw material powder preparation: the electrolytic copper powder, atomized copper powder and copper alloy powder agglomerated and dispersed in S1 are stirred and mixed uniformly to prepare raw material powder; S3, injection molding: the S2 raw material powder and the plastic-based binder are subjected to high-temperature and high-speed internal kneading to obtain high-purity feedstock; the high-purity feedstock is then injection molded to obtain a green part with no defects, no deformation, and uniform composition; the green part is then subjected to catalytic degreasing and thermal degreasing to obtain a thermally degreased sample; S4, atmospheric pressure sintering + hot isostatic pressing sintering: The sample after hot stripping in S3 is subjected to atmospheric pressure sintering in a hydrogen atmosphere and hot isostatic pressing sintering in a nitrogen atmosphere in turn to obtain a fully dense high thermal conductivity copper heat dissipation material.
2. The method for preparing high thermal conductivity copper heat dissipation material by injection molding according to claim 1, characterized in that: During the S1 air flow crushing process, the rotating speed of the classifying wheel is 9000-12000r / min; during the grinding process, 0.5% by mass of anhydrous ethanol and 1-1.5% of stearic acid are added, the electrolytic copper powder is ground at a pressure of 400-800Kpa, and the feed rate is 30-60g / min.
3. The method for preparing high thermal conductivity copper heat dissipation material by injection molding according to claim 1, characterized in that: The average particle size of the agglomerated and dispersed electrolytic copper powder in S1 is 15-25 μm.
4. The method for preparing high thermal conductivity copper heat dissipation material by injection molding according to claim 1, characterized in that: In the S2 raw material powder, the mass fraction of electrolytic copper powder is 20-40%, the mass fraction of atomized powder is 70-90%, and the mass fraction of copper-nickel alloy powder is 1-2%.
5. The method for preparing high thermal conductivity copper heat dissipation material by injection molding according to claim 1, characterized in that: The particle size of S2 electrolytic copper powder is less than or equal to 600 mesh, and D50 is 15-20µm; the particle size of atomized copper powder is 200-400 mesh, and D50 is 25-30µm; the copper alloy powder is copper-nickel alloy, in which the mass fraction of nickel is 60%, the mass fraction of copper is 33%, and the mass fraction of iron is 7%.
6. The method for preparing high thermal conductivity copper heat dissipation material by injection molding according to claim 1, characterized in that: The mass fraction of polyoxymethylene in the plastic-based binder in S3 is 75-85%, the mass fraction of polyethylene is 8-10%, the mass fraction of polypropylene is 4-6%, the mass fraction of ethylene-vinyl acetate copolymer is 4-6%, and the mass fraction of stearic acid is 4-6%; argon is selected as the protective atmosphere for the mixing atmosphere.
7. The method for preparing high thermal conductivity copper heat dissipation material by injection molding according to claim 1, characterized in that: During the S3 injection process, the injection temperature is 180-190℃, the injection pressure is 90-120bar, the injection speed is 40-80mm / s, and the mold temperature is 110-130℃; the main component of the binder removed by catalytic degreasing is polyoxymethylene; when thermal degreasing is performed from room temperature to 500℃, the heating rate is 1℃ / min, and the temperatures are kept at 200℃, 350℃, and 500℃ for 30min respectively.
8. The method for preparing high thermal conductivity copper heat dissipation material by injection molding according to claim 1, characterized in that: The degreasing rate of the S3 samples after thermal degreasing is 7.5-9.0%, and the density is 5.20-5.80g / cm 3 .
9. The method for preparing high thermal conductivity copper heat dissipation material by injection molding according to claim 1, characterized in that: In the step of S4 atmospheric pressure sintering, the flow rate of the hydrogen gas is ≥ 2m 3 / min, the sintering temperature is 1060-1075℃, and the holding time is 4-6h; during hot isostatic pressing sintering, the temperature is kept at 900-950℃ for 1-3h in a nitrogen atmosphere.
10. The method for preparing high thermal conductivity copper heat dissipation material by injection molding according to claim 1, characterized in that: The density of S4 fully dense high thermal conductivity copper heat dissipation material is 99.5-99.9%, the tensile strength is 185-210MPa, the tensile strain at break is 40.5-48.2%, the thermal conductivity is 360-376 W / (m·K), and the electrical conductivity is 82.5-90.8% IACS.
Citation Information
Patent Citations
Method for preparing high-performance heat conducting tube copper powder
CN101966587A
Method for preparing copper radiating fins of gradient structures by means of injection forming
CN102554229A
Method for preparing high-strength and high-conductivity copper alloy through metal injection molding
CN111996405A
Heat treatment method for preparing high-strength and high-conductivity copper alloy
CN117926153A
Method for preparing copper alloy through metal powder injection molding and high-strength and high-conductivity copper alloy
CN116352087A